The response of Stecklings Age and Plant Spacing on Carrot Seed Quality and Production - Manik, Fatiani; Tarigan, Rasiska; Barus, Susilawati (Journal of Tropical Horticulture, 2020)
The quality of seed needs to be considered in carrot seed production to maintain its productivity. The research aims to find out the response of stecklings age and plant spacing on carrot seed quality and production. This research was held on July 2018 – April 2019 in Berastagi field trial (1340 m MSL). The experiment used Randomized Complete Block Design (RCBD) with two factors, i.e., stecklings age (2 and 3 months) and plant spacing (25, 50, 75, and 100 cm), replicated four times (32 experiment units), 10 plants from each experiment units were taken as samples. The result showed that stecklings age and plant spacing were affected to plant vegetative and generative stages. The combination of 2-month stecklings and 50 cm plant spacing increased the number of secondary umble, if compared to cultivation, which was generally used by the farmer (3-month stecklings and 25 cm plant spacing). The best quality of carrot seed was obtained from the combination of 3-month stecklings and 50 cm plant spacing.